PENGGUNAAN OBAT SITOSTATIKA PADA ANAK-ANAK YANG MELAKUKAN KEMOTERAPI DI RSUP Dr. SARDJITO YOGYAKARTA TAHUN 2010 - Maria Wisnu Donowati; Ayu Y.N. Pramodhawardani; Ika Lestari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: Approximately 11.000 new child cancer cases per annum. An appropriate cytostaticdrug regimen can worse renal function. Aims of this research to determine the use of cytotoxic inchildren chemotherapy based on GFR according Schwartz and CB formulas in RSUP Dr.Sardjito Yogyakarta 2010 period. Cytotoxic drugs include antibiotic and non antibioticcytotoxics. An observational descriptive evaluative study with retrospective design was done.Inclusion criteria were patient 0 12 years with creatinine serum data and exclusion criteriawere acute or chronic kidney failure with creatinine serum 5 mg/dL. The data taken werepatient's age, height, weight, and creatinine serum. Adjustment doses was evaluated based on2GFR 60 mL/min/1.73 m for cytotoxic drugs. Dose adjustment was evaluated according to DIHand BSA guidelines. Using 171 patient's datas with 160 cases of antibiotics prescription and 704cases of non antibiotics prescription. 1,8%; 5,6% cases of antibiotics prescription and 1,0%;3,6% cases of non antibiotics prescription required adjusment doses according to the Schwartzand CB formulas. Unappropriate doses were found for doxorubicine and bleomycine as cytotoxicantibiotics usage and etoposide, L-asparginase, dan cyclophosphamid as non cytotoxicantibiotics usage.Keywords : cytotoxic drugs, children, glomerular filtration rate, Schwartz formula, CounahanBarratt formula.